Comparative Analysis Of The Utilisation Of Electronic Commerce And Business In Polish E-shops In The Years 2009-2011; Komparatywna analiza wykorzystania handlu i biznesu elektronicznego w polskich e-sklepach w latach 2009-2011 - Tomasz Czajkowski; Grzegorz Szymanśki (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of the article is to present the results of research concerning the utilisation of different aspects of electronic commerce and business in Polish e-shops, based on a number of comparative analyses performed for the years 2009-2011. Some of the presented data concern also the year 2008. The most important aspects covered by the analyses are: international trade and exports of Polish e-shops, marketing aspects of online businesses, the infrastructure and safety of Polish e-shops, their financial results, and also actions planned in order to minimise the effects of the economic crisis. The main conclusions drawn from these analyses, as well as predictions for the future for the Polish e-market, are also presented. – – Celem artykułu jest zaprezentowanie wynikoẃ badand́otyczacych wykorzystania roźṅych aspektoẃ handlu i biznesu elektronicznego w polskich e-sklepach oraz ich komparatywnej analizy wykonanej dla lat 2009-2011. Niektoŕe zaprezentowane dane dotycza takzė roku 2008. Najwazṅiejsze aspekty poruszane w analizach to: miedzynarodowy handel i eksport polskich sklepoẃ internetowych, aspekty marketingowe biznesu internetowego, infrastruktura i bezpieczenśtwo polskich e-sklepoẃ oraz ich wyniki finansowe, a takzė działania, ktoŕe sa planowane w celu zminimalizowania skutkoẃ kryzysu gospodarczego. W artykule zaprezentowane sa roẃniezẇnioski z wykonanych analiz oraz przewidywania na przyszłosćd́otyczace polskiego e-rynku.
Keywords: 330; retail electronic commerce and electronic business; e-shops; ICT; Poland